Difference in oral microbiota composition between patients with stage 5 chronic kidney disease on hemodialysis and healthy controls - Gan, Yumian; Ruan, Dandan; Zeng, Quanzuan; Zhu, Yaobin; Hu, Yanan; Wu, Rong; Lin, Xinfu; Wu, Jiabin; Meng, Xiaorong; Luo, Jiewei; Gao, Meizhu; Chen, Xin (American journal of translational research, 2023)
Owing to the symbiotic relationship between the microbiota and the human body, the microbiome is considered a "second human genome". Microorganisms are inextricably associated with human diseases and can affect the host phenotype. In the present study, 25 female patients with stage 5 chronic kidney disease (CKD5) undergoing hemodialysis in our hospital and 25 healthy subjects were recruited. The structure of the oral microbiota of the study participants was analyzed using the MiSeq PE300 sequencing platform and high-throughput 16S rDNA sequencing. The microbiota was compared between the groups using QIIME and the stats package in R. In total, 1,336 operational taxonomic units (OTUs) were obtained, and the relative frequencies of 450 OTUs differed significantly between the two groups (P < 0.05), indicating that the samples were rich in OTUs. A comparison of β-diversity indicated a significant difference in the microbial community structure between the two groups (P < 0.05). These results indicated that the biological diversity of the oral microbiota was highly correlated with CKD5. In this experiment, 189 genera, with significant differences in abundance between the groups (P < 0.05), were found. Furthermore, differences in the structure of the oral microbiota were observed between the groups at the phylum, class, order, family, and genus levels. Collectively, an imbalance in the oral microbiota may accelerate the progression of CKD and cause additional complications.